ANALISIS PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN AKTVITAS PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA (BEI) PERIODE 2015-2018 - Anggraini, Suci; Widhiastuti, Rosalia Nansih (ITB Swadharma, 2020)
This study aims to determine the effect of Return on Assets, Current Ratio, Debt to Asset Ratio, Total Asset Turnover and Fixed Asset Turnover on firm value (Tobins-Q). The sample used in this study was a mining company listed on the Indonesia Stock Exchange from 2015 to 2018. The sampling technique used purposive sampling so that the selected samples were 11 companies. The method of data analysis in this research is panel data linear regression analysis using Eviews version 8 software. The results showed that the Debt to Asset Ratio variable partially had a negative and significant effect on firm value (Tobins-Q). While the Return on Asset, Current Ratio, Total Asset Turnover and Fixed Asset Turnover variables do not affect the value of the company (Tobins-Q)